Multiplex immunohistochemistry reveals cochlear macrophage heterogeneity and local auditory nerve inflammation in cisplatin-induced hearing loss - Bedeir, Mai Mohamed; Ninoyu, Yuzuru; Nakamura, Takashi; Tsujikawa, Takahiro; Hirano, Shigeru (Frontiers in Neurology, 2022)
Inner ear macrophages play a vital role in cochlear homeostasis. Recent studies have demonstrated the existence of macrophages at different sites of the cochlea, with increased cochlear infiltration as an inflammatory response mechanism to injury. However, current methods, such as conventional immunohistochemistry and flow cytometry, provide limited information about the diversity of cochlear macrophages. Recently, multiplex immunohistochemistry (mIHC) successfully identified the heterogeneity of immune cells in cancer tissue and thereby improved our understanding of the disease prognosis. In this study, we modified the mIHC technique for cochlear tissue and utilized it to investigate cochlear macrophage behavior and heterogeneity before and after exposure to ototoxic drugs such as cisplatin. Four-week-old C57BL/6N female mice were intraperitoneally injected with cisplatin at 5 mg/kg/day consecutively for 6 days. Their hearing levels were assessed before and after the injection. Their cochleae were harvested before (day 0) and on days 8 and 15 after the cisplatin injection. Paraffin-embedded sections were sequentially immunostained using macrophage surface markers to identify the different categories of macrophages. Each immunostaining cycle included incubation with primary antibody, incubation with secondary antibody, chromogenic staining, and image scanning. Thereafter, all antibodies were stripped out, and antigen retrieval was performed to prepare the tissue for the next cycle. The results revealed that activated cochlear macrophages were not entirely differentiated into M1 or M2 categories but into multi-marker M1/M2 mixed macrophages. Furthermore, the ratio of these mixed (M1/M2) macrophages to Iba1⁺ macrophages increased in the auditory nerve after cisplatin exposure, suggesting local auditory nerve inflammation. The increase in the population of activated macrophages in the auditory nerve region was concomitant with the temporary shift of hearing threshold on day 8 post-cisplatin injection. The findings of this study indicate the effectiveness of mIHC in identifying cochlear macrophage heterogeneity both in the resting state and after cisplatin exposure. Therefore, mIHC could be a powerful tool in cochlear immunology research. Our findings may provide new insights into the prevention of hearing loss associated with cisplatin exposure.